Factors influencing intention of muslim consumers in choosing islamic house financing in Bandar Rimbayu - Arman Khalid, Mohamad (2021)
Malaysia is one of the pioneers in Islamic Finance, and Islamic House Financing facility has been offered in Malaysia over the past 50 years. However, in comparison with the conventional housing loan counterparts, the market share of Islamic House Financing is relatively low. Therefore, this paper aims to study the factors that influence consumer intention in choosing Islamic House Financing. The theory of planned behaviour (TPB) has been adopted in this study, and factors such as attitude, subjective norm, perceived behavioural control, and religiosity, are analysed to determine intention among 227 Muslim in Bandar Rimbayu, Selangor. This study employs T-Test, ANOVA, Pearson Correlation, and Multiple Linear Regression Analysis to achieve the objective of this research. Findings indicated that there is a significant relationship between Muslims’ attitude, perceived behavioural control, and religiosity, which determines their intention in choosing Islamic House Financing. Perceived behaviour control is found to be the most significant determinant in influencing consumer intention. This study can be used as a starting point to understand what drives Muslim consumers to choose Islamic based House Financing products, in order to attract them to make Islamic based House Financing as their first choice. The result may also benefit investors such as real estate developers in marketing strategies for their residential projects. Besides, financial institutions and government agencies such as Lembaga Pembiayaan Perumahan Sektor Awam (LPPSA) would also benefit for the sustainability of Islamic financial market in Malaysia.